Phenotyping and Genotyping of Saprolegnia parasitica isolated from Diwaniyah River-Iraq - Al-Ameri, Kadhim H.A (Technium BioChemMed, 2024)
The current study included a study of the spread of Saprolegnia parasitica in the water of the Diwaniyah River, water samples were collected for three months from the Al-Furat Bridge area for three months August, September, and October, isolation was done by bait method. After that, diagnosis was made by the traditional method adopted to explain the appearance and was supported by molecular diagnosis by PCR. The results showed that the fungus S.parasitica was present in varying numbers and percentages according to the months of the study, the numbers increased with decreasing temperatures, as they were month of October was the highest month in terms of the number of isolates, as it reached 10, representing a percentage of 46%, while the month of September had 8 isolates, a percentage of 36%, and the month of August. It was the lowest, as it was 4, with a rate of 18%. The molecular study appeared that the diagnosis of all isolates was identical to the traditional diagnosis, which relies on the appearance of the fungus in plates and under an optical microscope, where the bands were at 568 bp.